Late-career unemployment has mixed effects in retirement. Issue 1 (2nd January 2019) - Voss, Maren Wright; Merryman, M. Beth; Crabtree, Lisa; Subasic, Kathy; Birmingham, Wendy; Wadsworth, Lori; Hung, Man
ABSTRACT: Paid work forms a pattern of occupational engagement that shifts during both unemployment and retirement. Similar to unemployment, the occupational disruption associated with involuntary retirement has been linked to poorer physical and mental health outcomes. To better understand the health impact of work transitions during the pre- and post-retirement years, 24 retired individuals with late-career unemployment were interviewed at the Huntsman World Senior Games in October 2016. Demographic data were collected. Braun and Clarke's (2006) approach was utilized to thematically analyse the interview data and interpretations were evaluated against existing theory. Themes identified included struggle, freedom, and transition, followed by resilience and a return to well-being, with mental health levels reported at national averages for the age group. Choice and autonomy in the retirement years contributed to resilience. Concepts of productivity and meaningful engagement shift during the retirement years toward wellness derived from purposeful occupation, suggesting that occupational models may need to reconsider concepts of productivity and purpose for this age group.